Psychological Stress and Chronic Disease Management During the COVID-19 Pandemic in Turkey: A Cross-Sectional Web-Based Study - İNCİRKUŞ, KÜBRA; Altan Sarıkaya, Nihan (Galenos Publishing House, 2024)
Objective: To determine the levels of chronic disease management and psychological stress in the era of pandemic, and to evaluate the relationship between them. Methods: In this cross-sectional study, the sample consisted of 233 patients with chronic diseases. The data were collected with Personal Information Form, the Coronavirus disease-19 (COVID-19) Related Psychological Distress scale (CORPD) and the Patient Assessment of Chronic Illness Care (PACIC) between April 05 and September 30, 2021. The data were collected online via Google Forms and analyzed using number, percent, standard deviation, mode, mean, median, Spearman's correlation, KruskalWallis, Mann-Whitney U, post-hoc multiple comparisons. Results: The mean CORPD score of the participants was 41.8710.12, and the mean PACIC score was 63.36 +/- 19.26. Male participants with high school degrees, with low-income and health perception and with respiratory diseases had significantly higher mean PACIC score. Female participants with high school degrees, with low-income perception and with cardiovascular diseases had significantly higher CORPD score (p<0.05). Conclusion: Research results showed that moderate psychological stress and suspicion had a positive and stimulating effect on patients' chronic disease management. It is recommended to evaluate the long-term effects of psychological stress, and its impact on chronic disease management in further research.
Türkiye’de COVID-19 Salgını Sırasında Psikolojik Stres ve Kronik Hastalık Yönetimi: Web Tabanlı Kesitsel Çalışma
Keywords: Covid-19; Pandemics; Psychological Stress; Disease Management; Chronic Diseases